The frequency of Duchenne muscular dystrophy/Becker muscular dystrophy and Pompe disease in children with isolated transaminase elevation: results from the observational VICTORIA study - Kansu, Aydan; Kuloglu, Zarife; Tümgör, Gökhan; Taşkın, Didem Gülcü; Dalgıç, Buket; Çaltepe, Gönül; Demirören, Kaan; Doğan, Güzide; Tuna Kırsaçlıoğlu, Ceyda; Arslan, Duran; Işık, İshak Abdurrahman and Demir, Hülya and Bekem, Özlem and Şahin, Yasin and Bayrak, Nevzat Aykut and Selimoğlu, Mukadder Ayşe and Yavuz, Sibel and Taşkaya, İbrahim Ethem and Altay, Derya and , the VICTORIA Study Group and Taşkın, Didem Gülcü and Bükülmez, Ayşegül and Demir, Arzu Meltem and Tokgöz, Yavuz and Kansu, Aydan and Kuloğlu, Zarife and Kırsaçlıoğlu, Ceyda Tuna and Ayyıldız, Hasret and Kutluk, Günsel and Başaran, Meryem Keçeli and Sezer, Oya Balcı and Özkan, Tanju Başarır and Özgür, Taner and Üstündağ, Gonca Handan and Somuncu, Eda and Tümgör, Gökhan and Yavuz, Sibel and İşlek, Ali and Hoşnut, Ferda Özbay and Şahin, Gülseren Evirgen and Arslan, Duran and Altay, Derya and Doğan, Yaşar and Deveci, Uğur and Dalgıç, Buket and Ceylan, Kamercan and Baştürk, Ahmet and Balamtekin, Necati and Arslan, Melike and Demir, Hülya and Gülşen, Hayriye Hızarcıoğlu and Doğan, Güzide and Comba, Atakan and Selimoğlu, Mukadder Ayşe and Varol, İlknur and; Sebahat and; et al. (Frontiers in Pediatrics, 2023)
Introduction Elevated transaminases and/or creatine phosphokinase can indicate underlying muscle disease. Therefore, this study aims to determine the frequency of Duchenne muscular dystrophy/Becker muscular dystrophy (DMD/BMD) in male children and Pompe disease (PD) in male and female children with isolated hypertransaminasemia. Methods This multi-center, prospective study enrolled patients aged 3–216 months with serum alanine transaminase (ALT) and/or aspartate transaminase (AST) levels >2× the upper limit of normal (ULN) for ≥3 months. Patients with a known history of liver or muscle disease or physical examination findings suggestive of liver disease were excluded. Patients were screened for creatinine phosphokinase (CPK) levels, and molecular genetic tests for DMD/BMD in male patients and enzyme analysis for PD in male and female patients with elevated CPK levels were performed. Genetic analyses confirmed PD. Demographic, clinical, and laboratory characteristics of the patients were analyzed. Results Overall, 589 patients [66.8% male, mean age of 63.4 months (standard deviation: 60.5)] were included. In total, 251 patients (188 male and 63 female) had CPK levels above the ULN. Of the patients assessed, 47% (85/182) of male patients were diagnosed with DMD/BMD and 1% (3/228) of male and female patients were diagnosed with PD. The median ALT, AST, and CPK levels were statistically significantly higher, and the questioned neurological symptoms and previously unnoticed examination findings were more common in DMD/BMD patients than those without DMD/BMD or PD (p < 0.001). Discussion Questioning neurological symptoms, conducting a complete physical examination, and testing for CPK levels in patients with isolated hypertransaminasemia will prevent costly and time-consuming investigations for liver diseases and will lead to the diagnosis of occult neuromuscular diseases. Trial Registration Clinicaltrials.gov NCT04120168.